From Wildflowers to Yetis: Exploring Aesthetic, Mystery, and Self in Kincaid’s and Chatwin’s Himalayan Narratives - Gautam, Pragya (Mindscape: A Journal of English & Cultural Studies, 2024)
Traveling to the Himalayas transcends the mere act of conquering towering peaks and navigating rugged terrain; it unfolds as a profound journey into the intertwined mysteries of nature-wildflowers, mythic creatures such as yetis-and, importantly, a transformative odyssey of self-discovery. This study critically examines Jamaica Kincaid’s Among Flowers: A Walk in the Himalaya alongside Bruce Chatwin’s On Yeti Tracks, focusing on how their narratives weave together the sublime and the enigmatic. Through comparative textual analysis, the article reveals the dual nature of the Himalayan journey as both an aesthetic immersion enriched by abundant flora and majestic landscapes, and as a mystical realm inhabited by folklore and myth. Both authors illustrate how their encounters with the Himalayas provoke a deep reevaluation of self and nature, shedding light on human curiosity, wonder, vulnerability, and transformation. For Kincaid and Chatwin, the Himalayan walk emerges not merely as a physical expedition but as a profound quest blending beauty and mystery in the search for identity.